Description of the Psychological Needs of Klitih Perpetrators in Yogyakarta Using Thematic Apperception Test (TAT) - Dessy Pranungsari; Muhammad Hidayat; Marina Yollanda; Miftah Maulidiyah (Journal of Educational, Health and Community Psychology, 2021)
This study aims to determine the psychological needs of klitih perpetrators in Yogyakarta. The main objective of this research was to describe the psychological needs of klitih perpetrators in Yogyakarta. This study’s participants consist of three males with the following criteria: (1) aged 18-24, (2) klitih perpetrators, and (3) lives in Yogyakarta. The research method used was qualitative research using a phenomenological approach. Data collection was conducted using the Personality Test (TAT), equipped with an interview. Data analysis was conducted using thematic analysis. The findings reveal five dominant psychological needs of klitih perpetrators, such as the need for warmth and support (need for affiliation) and the need to seek help or sympathy (need for succorance). The need for freedom (need for autonomy) appeared to emerge strongly against the pressure from permissive and less warm family background, causing the participant to spend more time outside their homes. The need for violence (need for aggression) and the need for recognition (need for achievement) also appeared to arise due to the social environment’s demands, which then influence the participant to commit acts of klitih. This research shows the psychological needs of klitih perpetrators that can be channeled through other activities. Therefore, alternative positive activities that can meet these five primary needs should be developed to prevent adolescents from being involved in acts of klitih in schools, families, communities, and the Yogyakarta government.